Relationship between House Sanitation and Number of Bacterial in Bed Room with Pneumonia Case of Children Under Five Years Old in Kenjeran Sub District Surabaya - Fitria Nur Rahmawati (Universitas Airlangga, 2018)
The number of pneumonia cases in children under five years found in Surabaya city in 2016 was 3,925 cases (40.89%). The number of pneumonia cases in children under five years in Kenjeran sub district was highers with 232 cases. This study was purposed to analyze the relationship between house sanitation and airborne bacterial number with pneumonia cases in children under five years old in the Kenjeran sub district, Surabaya. This study was designed as a case control study using 12 cases and 12 controls as the samplers. This research was conducted in Kenjeran sub district and took place from May to November 2017. Statistical test was using by chi square and multivariate logistic regression. The results of the study was that the cases of p neumonia in children under five years old were birth weight (p=0,01), nutritional status (p=0,01), sanitation house (p=0,03) and airborne bacterial number (p=0,01). Multivariate logistic regression test results showed that significant variables were nutritional status and airborne bacterial number. Nutritional status have the significance 0.04 (p <α) with OR=15,00. Airborne bacterial number have the significance 0.04 (p <α) with OR=15,00. The conclusion of this study is nutritional status and airborne bacterial number are associated with pneumonia under five years old. It is highly suggested to improve the quality of home health and child care.